Jewish philosophy for the twenty-first century : personal reflections - Tirosh-Samuelson, Hava, 1950-; Hughes, Aaron W., 1968- (Supplements to The Journal of Jewish Thought and Philosophy, 2014)
Jewish Philosophy for the Twenty-First Century encourages contemporary Jewish thinkers to reflect on the meaning of Judaism in the modern world by connecting these reflections to their own personal biographies. In so doing, it reveals the complexity of Jewish thought in the present moment. The contributors reflect on a range of political, social, ethical, and educational challenges that face Jews and Judaism today and chart a path for the future. The results showcase how Jewish philosophy encompasses the methodologies and concerns of other fields such as political theory, intellectual history, theology, religious studies, anthropology, education, comparative literature, and cultural studies. By presenting how Jewish thinkers address contemporary challenges of Jewish existence, the volume makes a valuable contribution to the humanities as a whole, especially at a time when the humanities are increasingly under duress for being irrelevant.